1982
DOI: 10.1063/1.863620
|View full text |Cite
|
Sign up to set email alerts
|

Onset of convection in impulsively heated or cooled fluid layers

Abstract: Energy stability theory is employed to determine lower bounds on onset times and global stability bounds for initially isothermal fluid layers subjected to impulsive changes in surface temperature. Various combinations of rigid and free boundary conditions and heating or cooling are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 1 publication
5
26
0
Order By: Relevance
“…The last two models require the initial conditions at the heating time t = 0 and the criterion to define manifest convection. Energy method also has applied into this problem [6][7][8]. Even though energy method requires much computational load, it gives only a lower bound for the onset of the instability and * Corresponding author.…”
Section: Introductionmentioning
confidence: 98%
“…The last two models require the initial conditions at the heating time t = 0 and the criterion to define manifest convection. Energy method also has applied into this problem [6][7][8]. Even though energy method requires much computational load, it gives only a lower bound for the onset of the instability and * Corresponding author.…”
Section: Introductionmentioning
confidence: 98%
“…He also claimed that, for the cases when Ma c varied monotonically with time, the optimal stability boundary remained the same even if dk=dt > 0. Neitzel [8] reported that there existed cases where Ma c did not decrease with time monotonically (i.e. the stability curve reached a minimum first and then began to increase toward a steady-state limit) and care had to be taken for this situation.…”
Section: The Strong Global Stabilitymentioning
confidence: 97%
“…To resolve these deficiencies, the energy method seems to be very promising. Homsy [7] employed the energy method (corrected later by Neitzel [8]) to analyze the stability of a liquid layer heated or cooled impulsively. The region of finiteamplitude convection was demarcated in a Rayleigh number-time plane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 It is one of the aims of this paper to show that these conflicting conditions can lead to results which have a rigorous mathematical justification. When quasi-steady theory is inapplicable, energy-stability theory provides an alternative approach and this technique has been employed in a range of other papers [13][14][15] concerned with both centrifugal and thermal instabilities.…”
Section: Introductionmentioning
confidence: 99%